Bullitt - McQueen, Steve, 1930-1980.; Vaughn, Robert, 1932-; Bisset, Jacqueline, 1944-; Gordon, Don, 1926-; Duvall, Robert; Oakland, Simon; Fell, Norman, 1924-1998.; Brown, Georg Stanford; Trustman, Alan.; Kleiner, Harry; D'Antoni, Philip, 1929-; Yates, Peter, 1929-2011.; et al. (Burbank, CA : Warner Home Video, 1968)
A star witness in a controversial court case is murdered and the police detective assigned to guard him goes after the killers himself.
Based on the novel: Mute witness / Robert L. Pike.
Videodisc release of the 1968 motion picture.
"Disc 1: the movie"--Disc surface.
Special features: Commentary by director Peter Yates; theatrical trailer.
Director of photography, William A. Fraker ; film editor, Frank P. Keller ; music by Lalo Schifrin.
Steve McQueen, Robert Vaughn, Jacqueline Bisset, Don Gordon, Robert Duvall, Simon Oakland, Norman Fell, Georg Stanford Brown.
Keywords: Witnesses -- Protection -- Drama; Detective and mystery plays; Police -- California -- San Diego -- Drama; Murder -- Investigation -- Drama; Feature films; Thrillers (Motion pictures); Detective and mystery films; Films for the hearing impaired; Video recordings for the hearing impaired; Film adaptations